2019
DOI: 10.1080/21505594.2019.1620062
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus argenteus and Staphylococcus schweitzeri are cytotoxic to human cells in vitro due to high expression of alpha-hemolysin Hla

Abstract: Staphylococcus argenteus and Staphylococcus schweitzeri are newly identified species of the S. aureus -related complex. S. argenteus, as occurring globally and showing significant prevalence and comparable infection and morbidity rates compared to S. aureus , is becoming clinically important. Whole genome sequencing has revealed the presence of several virulence genes but the molecular mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
(70 reference statements)
0
8
1
Order By: Relevance
“…In contrast to our results, Johansson, Rautelin [ 49 ] demonstrated that S. aureus isolates were not cytotoxic to HeLaor HT29 cells. Also, El-Housseiny, Aboulwafa [ 50 ] showed that the cell-free supernatants of the four E. coli isolates caused nearly no cytotoxicity after 3 h of Vero cell infection.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Johansson, Rautelin [ 49 ] demonstrated that S. aureus isolates were not cytotoxic to HeLaor HT29 cells. Also, El-Housseiny, Aboulwafa [ 50 ] showed that the cell-free supernatants of the four E. coli isolates caused nearly no cytotoxicity after 3 h of Vero cell infection.…”
Section: Discussioncontrasting
confidence: 99%
“…Checking the sequence specificity of the first 300 aa of NWMN_1649 (BAF67921.1) of S. aureus indicated that the region between aa 46 to 157 looked distinct from the closest match ( Figure 1 a). Performing a BlastP search using the selected polypeptide against genus Staphylococcus while excluding S. aureus returned few hits from staphylococcal species not known to cause major human infections, if any, such as S. schweitzeri, S. argenteus, and S. sciuri ( Figure 1 b) [ 36 , 37 ]. Multiple sequence alignment using Clustal Omega of the selected peptide and its closest matches from the BlastP analysis ( Figure 1 c), and phylogenetic tree analysis ( Figure S1 ) confirmed that the S. aureus NWMN_1649 (BAF67921.1) 112 aa (46–157) peptide is distinct from its closest matches from other species.…”
Section: Resultsmentioning
confidence: 99%
“…When these data were further analyzed with DESeq2, S. argenteus was found to be more abundant in CTCL lesions than in normal-appearing healthy skin [61]. As S. argenteus can induce a 4-to 6-fold increase in the level of alpha-hemolysin exotoxin compared to S. aureus [62], the authors have suggested the possible pathogenic role of S. argenteus in CTCL. Further large-scale studies are needed to determine whether these bacteria are associated with the pathogenesis or the clinical course of CTCL.…”
Section: Cutaneous T Cell Lymphomamentioning
confidence: 99%